2006
DOI: 10.1212/01.wnl.0000200778.65597.ae
|View full text |Cite
|
Sign up to set email alerts
|

IM interferon β-1a delays definite multiple sclerosis 5 years after a first demyelinating event

Abstract: These results support the use of IM interferon beta-1a after a first clinical demyelinating event and indicate that there may be modest beneficial effects of immediate treatment compared with delayed initiation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…Follow-ups occurred on days 4, 15, and 30, weeks 7, 13, and 19, months 6 and 12, and then yearly [19]. The Controlled High Risk Avonex Multiple Sclerosis Prevention Study in Ongoing Neurologic Surveillance (CHAMPIONS) study was an open-label extension of Controlled High Risk Subjects Avonex Multiple Sclerosis Prevention Study (CHAMPS) [20], [21]. CHAMPS enrolled subjects without a prior episode of neurologic dysfunction who were seen within 27 days of the onset of neurologic symptoms consistent with MS and had an abnormal brain MRI (≥2 clinically silent MS-consistent lesions).…”
Section: Methodsmentioning
confidence: 99%
“…Follow-ups occurred on days 4, 15, and 30, weeks 7, 13, and 19, months 6 and 12, and then yearly [19]. The Controlled High Risk Avonex Multiple Sclerosis Prevention Study in Ongoing Neurologic Surveillance (CHAMPIONS) study was an open-label extension of Controlled High Risk Subjects Avonex Multiple Sclerosis Prevention Study (CHAMPS) [20], [21]. CHAMPS enrolled subjects without a prior episode of neurologic dysfunction who were seen within 27 days of the onset of neurologic symptoms consistent with MS and had an abnormal brain MRI (≥2 clinically silent MS-consistent lesions).…”
Section: Methodsmentioning
confidence: 99%
“…The manufacturer's submission stated that 30 µg of IM IFN-β-1a weekly is effective in reducing the relapse rate and disability progression compared with placebo, citing the MSCRG trial 200 and its observational extension 236 as evidence. The submission further stated that 30 µg of IM IFN-β-1a weekly is effective in delaying CDMS in patients with CIS, citing the CHAMPS trial 172 and its open-label extension 237 in support of this.…”
Section: Summary Of the Teva Pharmaceutical Industries Submissionmentioning
confidence: 99%
“…Several major placebo-controlled clinical trials, ETOM,9 CHAMPS,10 BENEFIT,11 and PreCISe,12 have shown that interferon (IFN) β-1a (Rebif ® ; EMD Serono, Inc., Rockland, MA, USA) (Avonex ® ; Biogen Idec, Cambridge, MA, USA), IFN β-1b (Betaseron ® ; Bayer Healthcare Pharmaceuticals, Inc., Montville, NJ, USA), or glatiramer acetate (Copaxone ® ; TEVA Neuroscience, Inc., Kansas City, MO, USA) therapy in CIS patients postpones the time to clinically definite multiple sclerosis for some. A 3-year extension of the BENEFIT13 study and a 5-year extension of the CHAMPS study, CHAMPION,14 have confirmed benefits of early treatment.…”
Section: Epidemiologymentioning
confidence: 84%